Strategi Tata Kelola Pemerintah Daerah dalam Meningkatkan Kapasitas Inovasi Daerah di Kabupaten Sidenreng Rappang - Muh. Wahyu. M; Haeruddin Syarifuddin; Sandi Lubis (Yayasan Literasi Sains Indonesia, 2025)
This research provides an empirical contribution to the strengthening of strategic governance-based innovation policies, and can serve as a practical reference for other regions facing similar innovation problems. This study aims to analyze the effect of local government management strategies on increasing regional innovation in Sidenreng Rappang Regency. Using a quantitative approach with descriptive methods, data was collected through observation, questionnaires, and literature studies from 39 respondents at Bapperida. The results of validity and reliability tests showed that the instruments used were valid and reliable. Regression analysis revealed that planning, organizing, directing and supervising have a positive and significant effect on regional innovation (R² = 0.811). The t-test and F-test reinforced that all independent variables simultaneously contributed significantly. These findings support George R. Terry's theory and the Regional Innovation System approach that emphasizes the importance of managerial synergy in public governance. The practical implications of the results emphasize the need for strategic integration of management functions to strengthen regional innovation capacity. However, the limitations of the study lie in the scope of the region and the quantitative approach that has not captured contextual aspects thoroughly. It is recommended for future research to use a mixed methods approach and a wider area coverage for more in-depth and generalizable results.